The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1038/358328a0
|View full text |Cite
|
Sign up to set email alerts
|

Association of tyrosine kinase p56lck with CD4 inhibits the induction of growth through the αβ T-cell receptor

Abstract: The membrane glycoprotein CD4 enhances antigen-mediated activation of T cells restricted by class II molecules of the major histocompatibility complex (MHC). This positive function has been attributed to the protein tyrosine kinase p56lck (ref. 4), which is noncovalently associated with the cytoplasmic portion of CD4, and is activated on CD4 aggregation. Antigen presentation by MHC class II molecules coaggregates CD4 and the T-cell antigen receptor (TCR alpha beta-CD3). Thus, the mutual specificity of CD4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(92 citation statements)
references
References 42 publications
3
89
0
Order By: Relevance
“…On the other hand, the role of p56 ~k after stimulation with 46-61WW cannot be fully determined. Although it is clear that PLC'y1 phosphorylation can occur in the absence of the CD4 cytoplasmic tail, these data cannot rule out the involvement of p56 ~k as several studies have shown that it does not have to be associated with CD4 to exert its effect (42,43).…”
Section: Differential Signaling: Tcr Ligatio In the Absence Of Il-2 mentioning
confidence: 68%
See 1 more Smart Citation
“…On the other hand, the role of p56 ~k after stimulation with 46-61WW cannot be fully determined. Although it is clear that PLC'y1 phosphorylation can occur in the absence of the CD4 cytoplasmic tail, these data cannot rule out the involvement of p56 ~k as several studies have shown that it does not have to be associated with CD4 to exert its effect (42,43).…”
Section: Differential Signaling: Tcr Ligatio In the Absence Of Il-2 mentioning
confidence: 68%
“…However, p56 ~k has also been shown to perform important kinase-independent functions during T cell activation (37). Although previous studies have suggested that neither effective T call stimulation nor CD4-TCR association can occur when CD4 cannot associate with p56 ~k (38)(39)(40)(41), recent studies have implied an opposing view with p56 kk playing a critical role in TCR-mediated fignaling and T cell development in vivo in the absence of coupling to CD4 (42)(43)(44).…”
mentioning
confidence: 79%
“…CD4 can enhance the T cell response regardless of whether it binds to the same or to different MHC molecules as the TCR (2). The engagement of CD4 with ligand or anti-CD4 in solution can positively or negatively affect the outcome of TCR/CD3 stimulation, which appears to be dependent on the concentration of anti-CD4 Ab and the conditions used for costimulation of CD4 (57)(58)(59)(60)(61)(62). The inhibition of CD3/TCR signaling was also observed by cross-linking of CD4 incapable of Lck binding (equivalent to our 2C CD4) (62).…”
Section: Discussionmentioning
confidence: 99%
“…First, Lck is involved in ligandinduced TCR internalization and thus may regulate the availability of TCR and the magnitude of T cell signaling (7)(8)(9)(10)(11). Second, separate ligation of TCR and CD4 causes Lck activation and inhibits T cell responses by priming CD4 ϩ T cells for death (12,13).…”
Section: Superantigen Stimulation Reveals the Contribution Of Lck Tomentioning
confidence: 99%